PENINGKATAN LITERASI INVESTASI MELALUI EDUKASI SECURITIES CROWDFUNDING SEBAGAI ALTERNATIF PENDANAAN DAN INVESTASI DI ERA DIGITAL - Muhammad Abdul Muis; Suwardi Suwardi; Agus Amri Mokoginta; Aldilla Saeba (Jurnal Pengabdian Bukit Pengharapan, 2026)
The rapid advancement of digital technology has transformed the financial sector, leading to the emergence of various innovations in the capital market that provide broader access to investment and financing opportunities. One of these innovations is Securities Crowdfunding (SCF), a fundraising mechanism that enables businesses to offer securities to the public through electronic platforms licensed and supervised by the Financial Services Authority (OJK). Despite its significant potential to enhance financial inclusion and expand funding access for Micro, Small, and Medium Enterprises (MSMEs), public understanding of Securities Crowdfunding remains relatively limited. This community service program aimed to enhance investment literacy through education on Securities Crowdfunding as an alternative source of financing and investment in the digital era. The program was conducted through an educational seminar consisting of presentations, interactive discussions, and question-and-answer sessions. The topics covered included the fundamental concepts of Securities Crowdfunding, applicable regulations, investment mechanisms, potential benefits, investment risks, and its role as an alternative financing instrument for MSMEs. The results indicated that participants gained a better understanding of the characteristics of Securities Crowdfunding, investment procedures, and its contribution to supporting business growth. Furthermore, the activity increased participants’ awareness of the importance of investment literacy in responding to the rapid development of the digital financial industry. Therefore, Securities Crowdfunding education can serve as an effective approach to improving public investment literacy while encouraging the utilization of inclusive, transparent, and accessible capital market instruments.